Board compliance - Armour, J; Garrett, B; Gordon, J; Min, G (Minnesota Law Review, 2020)
What role do corporate boards play in compliance? Compliance programs are internal enforcement programs, whereby firms train, monitor and discipline employees with respect to applicable laws and regulations. Corporate enforcement and compliance failures could not be more high-profile, and have placed boards in the position of responding to systemic problems. Both case law on boards’ fiduciary duties and guidance from prosecutors suggest that the board should have a continuing role in overseeing compliance activity. Yet very little is actually known about the role of boards in compliance. This paper offers the first empirical account of public companies’ engagement with compliance at the board level, drawing on director-level data from BoardEx and data on federal organizational prosecutions from the Duke University and University of Virginia Corporate Prosecution Registry. We find that, despite a standard account that compliance has boomed, few boards actually adopt compliance committees. Less than five per cent of U.S. public companies have done so, although the proportion has grown steadily over time. We use our data to explore why boards establish compliance committees. Our results suggest that there is room for more constructive engagement with compliance by many boards. We conclude by recommending ways in which board compliance might be facilitated or encouraged: reconsidering norms about board size and independence, enhancing accountability of directors to regulators, and tightening state law fiduciary duties regarding oversight.